2019
DOI: 10.1186/s12935-019-1055-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA ABCB10 promotes hepatocellular carcinoma progression by increasing HMG20A expression by sponging miR-670-3p

Abstract: Background/aimsThe dysregulation of circABCB10 may play an critical role in tumor progression. However, its function in liver cancer (HCC) is still unclear. Therefore, this experimental design is based on circABCB10 to explore the pathogenesis of HCC.MethodsThe expression of circABCB10 and miR-670-3p in HCC tissues was detected by RT-qPCR. CCK-8, Brdu incorporation, colony formation and transwell assays were used to determine the effect of circABCB10 on HCC cell proliferation and migration. Target gene predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…13,14 For example, circABCB10 could promote HMG20A expression to enhance the proliferation and invasion of HCC by sponging miR-670-3p. 15 Also, circ_0001955 could accelerate the tumorigenesis of HCC via regulating the miR-516a-5p/TRAF6-MAPK11 network. 16 Therefore, circRNA may be an important biomarker for cancer therapy and may provide an important basis for elucidating the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 For example, circABCB10 could promote HMG20A expression to enhance the proliferation and invasion of HCC by sponging miR-670-3p. 15 Also, circ_0001955 could accelerate the tumorigenesis of HCC via regulating the miR-516a-5p/TRAF6-MAPK11 network. 16 Therefore, circRNA may be an important biomarker for cancer therapy and may provide an important basis for elucidating the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The Editor-in-Chief has retracted this article [1] due to lack of evidence that the study has received ethics approval. After publication it has come to the Editor's attention that in the body of the article the authors state that their study was approved by the First Hospital of Jilin University Research Ethics Committee.…”
mentioning
confidence: 99%
“…In another case, an insertion at chr1:228921863, located in a super-enhancer, was observed to be associated with increased expression of ABCB10 gene (corrected p-value = 3.7⋅10 − 3 ) and in the same causal set with rs61824911, a GWAS susceptibility locus for basal cell carcinoma (BCC) (Chahal et al 2016). Multiple studies have reported the gene ABCB10 as a susceptibility locus for different types of cancers, such as breast cancer, clear cell renal cell carcinoma, hepatocellular carcinoma, and epithelial ovarian cancer (Liang et al 2017;Chen et al 2019;Huang et al 2019;Fu et al 2019), and its increased expression has been reported in a retinoblastoma cell line (Hendig et al 2009). Future studies on SVs can contribute to deeper understanding on mechanism of disease.…”
Section: Discussionmentioning
confidence: 96%